15th European Microwave Conference, 1985 1985
DOI: 10.1109/euma.1985.333614
|View full text |Cite
|
Sign up to set email alerts
|

An Overview on Numerical Techniques for Modeling 3-Dimensional Passive Components

Abstract: A number of numerical techniques are described for the analysls of passive components. Fundamental concepts and typical applications are presented and discussed . A list of references is included for representative works reported in literature. INTRODUCTI ONAlthough numerical and analytical, if possible, characterizations and modelings of miniaturized passive components have been exercised by a large number of researchers and engineers for some time; the necessity of such activities are increasingly important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1985
1985
1999
1999

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…(4p2+w)2U0%er/32) fjzji I =0o (1) 2 d d with VT = a +t 2 dx dy and they have to verify the boundary conditions (periodicity, synumetry, ...etc) and the continuity conditions for their tangential components (zero tangential electric field at the dielectric-conductor interface, and equal electric and magnetic tangential fields at the interface between two different dielectrics). Once the eigen values kn are d%termined, at a given frequencyc,the eigen function Ez i and Hz,i can be determined from Maxwell's equations.…”
Section: Electromagnetic Analysis Of a Waveguide Using Spectral Domaimentioning
confidence: 99%
See 1 more Smart Citation
“…(4p2+w)2U0%er/32) fjzji I =0o (1) 2 d d with VT = a +t 2 dx dy and they have to verify the boundary conditions (periodicity, synumetry, ...etc) and the continuity conditions for their tangential components (zero tangential electric field at the dielectric-conductor interface, and equal electric and magnetic tangential fields at the interface between two different dielectrics). Once the eigen values kn are d%termined, at a given frequencyc,the eigen function Ez i and Hz,i can be determined from Maxwell's equations.…”
Section: Electromagnetic Analysis Of a Waveguide Using Spectral Domaimentioning
confidence: 99%
“…Many different methods of solution for these discontinuities have been suggested during the past 40 years and an overview on many of these methods are given in [1]. While, in general, some degree of approximation must be made in most of these methods, the Modal Analysis [2,3] provides an exact solution involving straightforward calculations which can easily be applied to a wide variety of structures.…”
Section: Introductionmentioning
confidence: 99%
“…The ai yield the absorption coefficients (Yk and the resonant frequency f k in equation (1). zl, z2, .…”
Section: Initial Conditions Giving the P Starting Values For S(n)mentioning
confidence: 99%
“…Excellent reviews of those methods can be found in [1] and [2]. Many of them explicitly or implicitly use the variational behavior of a parameter or a functional.…”
Section: Introductionmentioning
confidence: 99%
“…In both cases, the variational form is formulated either in the spatial domain or in the Fourier-transformed domain [8], using for this, the spectral-domain approach presented in [9] and [10]. To the best of our knowledge, and restricting our study to transmission-line parameters, implicit or explicit variational formulations exist only for propagation constants [1], [6], [8] and quasi-TEM inductances [11] or capacitances [12], [13], yielding values for the characteristic impedance under the restrictive quasi-transverse-electromagnetic (TEM) assumption. Such principles are missing for the characteristic impedance of nonquasi-TEM structures.…”
Section: Introductionmentioning
confidence: 99%